1993
DOI: 10.3758/bf03197991
|View full text |Cite
|
Sign up to set email alerts
|

Learning to recalibrate the role of dead reckoning and visual cues in spatial navigation

Abstract: In Experiment 1, hamsters started from their permanent home at the periphery of a circular arena and headed to a food source at the center. They then returned, fully laden with food, along a direct path to their home. On control trials, in which no manipulation takes place, visual cues outside the arena and dead reckoning (i.e., updated internal references generated during the outward journey to the food source) controlled the return journey. On experimental trials, the arena, with the hamster in its nest, was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 31 publications
2
15
0
Order By: Relevance
“…We also note that the rapidity with which rats learn to guide locomotor behavior using distant cues (Morris, 1981) is parallel to the immediacy and consistency with which the white cue card controls the angular position of firing fields. Similar demonstrations of the greater efficacy of distant cues relative to local cues or path integration information are provided by a large number of studies (Suzuki et al, 1980;Téroni et al, 1987;Etienne et al, 1993;Alyan and Jander, 1994).…”
Section: Comparison Of Place Cell Results With Behavioral Datasupporting
confidence: 65%
“…We also note that the rapidity with which rats learn to guide locomotor behavior using distant cues (Morris, 1981) is parallel to the immediacy and consistency with which the white cue card controls the angular position of firing fields. Similar demonstrations of the greater efficacy of distant cues relative to local cues or path integration information are provided by a large number of studies (Suzuki et al, 1980;Téroni et al, 1987;Etienne et al, 1993;Alyan and Jander, 1994).…”
Section: Comparison Of Place Cell Results With Behavioral Datasupporting
confidence: 65%
“…For this rat, the cue control was so strong that it often overrode the rat's internal direction sense even when the rat was not disoriented and could presumably tell that the card was in a different location each session. These combined results indicate that, in many rats, it is difficult to overcome the prior learning effects regarding the perceived stability of the visual cue, similar to behavioral results in hamsters reported by Etienne et al (1993).…”
Section: Effects Of Retrainingsupporting
confidence: 78%
“…Similar to observations of navigation in mammals (e.g., Etienne et al, 1993;Knierim et al, 1998;Shettleworth & Sutton, 2005;Whishaw & Tomie, 1997), apparently stable landmarks reset the orientation of the human path integrator, whereas detectably unstable landmarks precipitate a switch from landmark navigation to path integration.…”
Section: Comparison To Animal Navigationmentioning
confidence: 48%
“…Just as a stable environment temporarily suppressed the functions of path integration in Experiments 1 and 2, leading to reliance on landmark navigation, here a chronically unstable environment temporarily suppresses landmark navigation and leads to reliance on path integration. Previous research has also reported that humans and animals change from landmark navigation to path integration due to cue conflicts produced by large landmark shifts (Barry, Hayman, Burgess, & Jeffery, 2007;Etienne, Lambert, Reverdin, & Teroni, 1993;Shettleworth & Sutton, 2005;Whishaw & Tomie, 1997;Zhao & Warren, 2015; see also Ratliff & Newcombe, 2008). But in the present experiment there was no cue conflict during catch trials, for visual landmarks and path integration were congruent -yet landmarks were ignored in early catch trials nonetheless.…”
Section: Discussionmentioning
confidence: 99%